Epoxidation of karanja (Millettia pinnata) oil methyl esters in the presence of hydrogen peroxide over a simple niobium-containing catalyst - Scotti, Nicola; Ravasio, Nicoletta; Evangelisti, Claudio; Psaro, Rinaldo; Penso, Michele; Niphadkar, Prashant S.; Bokade, Vijay V.; Guidotti, Matteo (Catalysts, 2019)
The synthesis, characterization and catalytic performance of a conceptually simple, novel NbOx-SiO2 catalyst are here described. The niobium(V)-silica catalyst was prepared starting from cheap and viable reactants, by alkaline deposition of NH4Nb(C2O4)(2)H2O in the presence of fructose as a stabilizer and subsequent calcination. The NbOx-SiO2 solid (0.95 Nb wt.%) was tested in the liquid-phase epoxidation with aqueous hydrogen peroxide of methyl oleate, as a model substrate. It was then tested in the epoxidation of a mixture of methyl esters (FAMEs) obtained by transesterification with methanol and purification of karanja oil, extracted from the autochthonous Indian variety of Millettia pinnata tree. The catalyst showed a promising performance in terms of methyl oleate conversion (up to 75%) and selectivity to epoxide (up to 82%). It was then tested on the FAME mixture from karanja oil, where interesting conversion values were attained (up to 70%), although with lower selectivities and yields to the mixture of desired epoxidized FAMEs. The solid withstood four catalytic cycles overall, during which a non-negligible surface reorganization of the Nb(V) sites was observed. However, this restructuring did not negatively affect the performance of the catalysts in terms of conversion or selectivity.
Keywords: epoxidation; fatty acid methyl esters; heterogeneous catalysis; Hydrogen peroxide; karanja oil; mesoporous silica catalyst; Millettia pinnata; niobium catalysts